Icebreaking polar class research vessels: New Antarctic fleet capabilities ... : سفن الأبحاث القطبية لكسر الجليد: قدرات أسطول أنتاركتيكا الجديدة ... - Michelle Rogan-Finnemore; Miguel A. Ojeda; Jorge Manuel Paz Acosta; Patrice Bretel; Nick Browne; Stig Flått; Shuoren Wang; Randolph Sliester (OpenAlex, 2021)
Abstract Supporting Antarctic scientific investigation is the job of the national Antarctic programmes, the government entities charged with delivering their countries' Antarctic research strategies. This requires sustained investment in people, innovative technologies, Antarctic infrastructures, and vessels with icebreaking capabilities. The recent endorsement of the International Maritime Organization (IMO) Polar Code (2015) means that countries must address challenges related to an ageing icebreaking vessel fleet. Many countries have recently invested in and begun, or completed, builds on new icebreaking Polar research vessels. These vessels incorporate innovative technologies to increase fuel efficiency, to reduce noise output, and to address ways to protect the Antarctic environment in their design. This paper is a result of a Council of Managers of National Antarctic Programs (COMNAP) project on new vessel builds which began in 2018. It considers the recent vessel builds of Australia's RSV Nuyina, ... : إن دعم البحث العلمي في أنتاركتيكا هو مهمة البرامج الوطنية في أنتاركتيكا، وهي الكيانات الحكومية المكلفة بتنفيذ استراتيجيات البحث في أنتاركتيكا في بلدانها. وهذا يتطلب استثمارًا مستدامًا في الأشخاص والتقنيات المبتكرة والبنى التحتية في أنتاركتيكا والسفن ذات قدرات كسر الجليد. ويعني الإقرار الأخير للمدونة القطبية للمنظمة البحرية الدولية (2015) أنه يجب على البلدان مواجهة التحديات المتعلقة بأسطول سفن كسر الجليد المتقادم. استثمرت العديد من البلدان مؤخرًا وبدأت أو أكملت بناء سفن أبحاث قطبية جديدة لكسر الجليد. تتضمن هذه السفن تقنيات مبتكرة لزيادة كفاءة استهلاك الوقود، وتقليل إنتاج الضوضاء، ومعالجة طرق حماية بيئة أنتاركتيكا في تصميمها. هذه الورقة هي نتيجة لمشروع مجلس مديري البرامج الوطنية لأنتاركتيكا (COMNAP) بشأن بناء السفن الجديدة الذي بدأ في عام 2018. وهي تنظر في بناء السفن الأخيرة من RSV Nuyina في أستراليا، و MV Xue Long 2 في الصين، و L'Astrolabe في فرنسا، و RV Kronprins Haakon في النرويج، و BAP Carrasco في بيرو، و RRS Sir David Attenborough في المملكة المتحدة. تقدم الورقة أمثلة على النظر الهادف في متطلبات الدعم ...